Neonatal Screening in Europe Revisited: An ISNS Perspective on the Current State and Developments Since 2010 - J. Gerard Loeber; Dimitris Platis; Rolf H. Zetterström; Shlomo Almashanu; François Boemer; James R. Bonham; Patricia Borde; Ian Brincat; David Cheillan; Eugenie Dekkers; Dobry Dimitrov; Ralph Fingerhut; et al. (MDPI AG, 2021)
Neonatal screening (NBS) was initiated in Europe during the 1960s with the screening for phenylketonuria. The panel of screened disorders ("conditions") then gradually expanded, with a boost in the late 1990s with the introduction of tandem mass spectrometry (MS/MS), making it possible to screen for 40-50 conditions using a single blood spot. The most recent additions to screening programmes (screening for cystic fibrosis, severe combined immunodeficiency and spinal muscular atrophy) were assisted by or realised through the introduction of molecular technologies. For this survey, we collected data from 51 European countries. We report the developments between 2010 and 2020 and highlight the achievements reached with the progress made in this period. We also identify areas where further progress can be made, mainly by exchanging knowledge and learning from experiences in neighbouring countries. Between 2010 and 2020, most NBS programmes in geographical Europe matured considerably, both in terms of methodology (modernised) and with regard to the panel of conditions screened (expanded). These developments indicate that more collaboration in Europe through European organisations is gaining momentum. We can only accomplish the timely detection of newborn infants potentially suffering from one of the many rare diseases and take appropriate action by working together.